ASSESSMENT BY THE PEDAGOGICAL COMMUNITY OF INCLUSIVE COMPETENCIES OF SPECIAL TEACHERS - Билялов, Д.Н.; Мовкебаева, З.А.; Дузелбаева, А.; Хамитова, Д.С. (Pedagogy and Psychology, 2023)
The article is devoted to the issues of the readiness of special teachers to work in the conditions of inclusive education. The current state and problems of the formation of inclusively oriented professional competencies of special teachers are analyzed. The importance of inclusive competencies for special teachers for successful work in the general education process is proved, the necessity of systematic and comprehensive pedagogical activities for the formation of these competencies is substantiated. The article presents brief results of a specially organized interviewing of the administration and teachers of secondary schools of Pavlodar and Pavlodar region, the purpose of which was to identify their opinions on the level of readiness and formation of inclusively oriented professional competencies of special teachers. It was determined that teachers and the administration of general education organizations attributed to the professional qualities of a special teacher who effectively implements his activities in an inclusive education: competence, pedagogical ethics, practical skills, understanding and acceptance of a child with disabilities, flexibility and adaptability, the ability to adapt in accordance with the characteristics of the child or the educational situation, sociability and willingness to cooperate, emotional stability and stress resistance, skills of working in an interdisciplinary team, responsibility, diligence, availability of certain organizational skills, etc. The article was prepared within the framework of the program-targeted financing of the Ministry of Science and Higher Education of the Republic of Kazakhstan BR18574162 "Inclusively oriented training of special teachers".